Remarks on the zeros of quadratic coquaternionic polynomials - Falcão, M. I. (2022)
In this paper we focus on the study of monic quadratic polynomials whose coefficients are coquaternions and present several new results concerning the number and nature of its zeros. Examples specially constructed to illustrate the diversity of cases that can occur are also presented.